Answer:
<em>3^2 ; Option B</em>
Step-by-step explanation:
We are given the equation 3^ -6 * ( 3^4 / 3^0 )^2, which can be solved through the application of exponential rules;
<em>3^2 ; Option B</em>
Answer:
y = x + 7
Step-by-step explanation:
the equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y-intercept )
here m = , hence
y = x + c ← is the partial equation
to find c substitute (4, 9) into the partial equation
9 = 2 + c ⇒ c = 9 - 2 = 7
y = x + 7 ← equation in slope-intercept form
Answer:
Gyeyuegtee2ugt2egt2fekufwetuifkueyr2v4xtk63ur Gyeyuegtee27gt2egt2fwk7fwet7ifkue6r2v4ftk63 trviugrxrt6uk3 gtyr7ix txyt 4t ulu66tt xflut I r t4e1ttrxl86vt4tt6tr63t3r6te3y2tyewdgydgey3dgyywgewsyfwdgy
When you have two squares stacked on top of each other, pretend the angle in the bottom left of the top square is a 90 degree angle, that means that the angle of the square right underneath, also sharing the line, is a 90 degree angle. Or whatever you would need to get it equal to 180, my example was 90/90.